The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3904/kjim.2015.30.1.62
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic differences with and without ozone-exposure in a smoking-induced emphysema lung model

Abstract: Background/AimsAcute exacerbations in chronic obstructive pulmonary disease may be related to air pollution, of which ozone is an important constituent. In this study, we investigated the protein profiles associated with ozone-induced exacerbations in a smoking-induced emphysema model.MethodsMice were divided into the following groups: group I, no smoking and no ozone (NS + NO); group II, no smoking and ozone (NS + O); group III, smoking and no ozone (S + NO); and group IV, smoking and ozone (S + O). Bronchoal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…treatment. Therefore, TBC1D5 may be a useful biomarker for ozone-induced lung injury in patients with emphysema [ 149 ].…”
Section: Introductionmentioning
confidence: 99%
“…treatment. Therefore, TBC1D5 may be a useful biomarker for ozone-induced lung injury in patients with emphysema [ 149 ].…”
Section: Introductionmentioning
confidence: 99%
“…TBC family proteins containing the TRE2/Bub2/CDC16 domain are highly conserved in eukaryotic cells [ 33 ]. Commonly, these proteins were considered as GTPase activating proteins (GAPs) of the Rab small GTPase family proteins [ 34 , 35 ]. TBC1D5 is lowly expressed in ccRCC, and the expression level is significantly associated with prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Eno3 is upregulated in traumatic brain injury [44]. The expression of triosephosphate isomerase 1 (Tpi1) is low in smoking-induced emphysema lung models [45]. It is worth mentioning that Tpi1 is involved in the glycolysis or gluconeogenesis pathway in acute lung injury [46].…”
Section: Discussionmentioning
confidence: 99%